Penerapan Reinventing Government (Mewirausahakan Birokrasi) di Kecamatan Jekan Raya Kota Palangka Raya - Siren Siren; Irwan Sinaga (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The purpose of this study was to find out the application of the Reinventing Government in the District of Jekan Raya, Palangka Raya City. The method used in this study is a qualitative research method, using interview data collection techniques, documentation, and observation. The data sources in this study were the Sub-District Head and his staff and the community in the administrative area of ​​Jekan Raya Sub-District. Based on the results of the study show that the implementation of the Reinventing Government in Jekan Raya Subdistrict, Palangka Raya City is still not done maximally and consistently. Of the ten Reinventing Government principles, it turns out that only three policies have been correctly implemented, namely the Results-Oriented law, Anticipatory Government, and Decentralized Government. The other seven principles that have not been consistently applied are the principles of Catalyst Government, Community Ownership, Competitive Government, Mission Oriented Government, Customer Oriented Government, Entrepreneurial Governance, and Market-Oriented Government. Subdistricts should be able to foster interest in the community so that they can actively participate in district programs/activities, can take the initiative to collaborate with other agencies to conduct socialization to the community, employees appointed directly to manage suggestion boxes, can respond to community aspirations, are mission-oriented , providing truly excellent services, reducing and eradicating extortion practices, more carefully in seeing more productive potentials, and providing various information related to sub-districts through multiple media